Spent coffee grounds enhanced compressive strength of cement mortar: an optimization study - Yee, Jia Jun; Khong, Sheh Ching; Tee, Kong Fah; Jolius, Gimbun; Chin, Siew Choo (Springer, 2024)
This paper presents an optimization study of spent coffee grounds (SCG) as cement mortar additives to enhance mortar strength. In recent years, sustainable materials have begun finding their way into cement mortar, with SCG being one. There is limited optimization study on the SCG addition in mortars, hence this study was performed to optimize the curing time and SCG addition in cement mortar to achieve the highest compressive strength through response surface methodology. Scanning Electron Microscopy (SEM) characterization was carried out on the SCG particles to identify their physical properties. An Energy Dispersive X-ray (EDX) analysis was carried out to identify its chemical properties. Simultaneously, a workability test, the flow table test, is conducted to study the effect of SCG on the flowability of the cement mortar mixes. The synergistic effect between SCG content in cement mortar mixes and the curing period was statistically studied and analyzed. Both parameters were then optimized to obtain the best performance mix of SCG in cement mortar. It was found that 1.1% SCG and a curing day of 68 days produced the highest compressive strength (33.4MPa) of cement mortar. The Response Surface Methodology (RSM)-optimized cement mortar mix presented at least a 12.62% improvement in compressive strength from control cement mortar without SCG additives (28.77MPa). Experimental validation of the optimum condition showed a good agreement with a deviation of 3.12% in three replicates, thus indicating that the optimum model in this work can be used to model the compressive strength of the SCG-cement mortar mixture.